PENGARUH PENGETAHUAN PEMAHAMAN PERATURAN PAJAK, PELAYANAN FISKUS, PERSEPSI EFEKTIVITAS SISTEM PERPAJAKAN TERHADAP KEMAUAN MEMBAYAR PAJAK - Manuaba, Ida Ayu Candra Apsari; Gayatri, Gayatri (E-Jurnal Akuntansi, 2017)
Taxes have a large role in the development of the country. One factor for the country's development can be realized well that enhance the willingness to pay taxes, which is still deemed less. The purpose of this study to determine the effect of knowledge and understanding of the tax rules, the service tax authorities and the perception of the effectiveness of the tax system on the willingness to pay taxes an individual taxpayer. The method used in this research is the method nonprobality sampling with purposive sampling technique. The analysis finds that the knowledge and understanding of tax rules a positive influence on the willingness to pay taxes an individual taxpayer, service fiskus positive influence on the willingness to pay taxes an individual taxpayer, and the perception of the effectiveness of the system taxation positive influence on the willingness to pay taxes an individual taxpayer.
Keywords: tax regulations, tax authorities services, perception